Important Factors of Preparing Students for Professional Activity on the Basis of Integration of Graphic Sciences (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article analyzes the important factors of preparing students for professional activity on the basis of the integration of graphic sciences and the results of research work carried out by several scientists in this field. On the basis of these analyzes, the integration of graphic disciplines was developed and a questionnaire on professional activities was conducted among students, and their results are also covered in the article. The teaching of graphic sciences, which is a key factor in the development of students in the field of graphic design, design and their integration, is based on clear evidence and conclusions and recommendations that in the future these personnel will play a key role in mastering the field and their professional activities.